Intestinal Perforation Secondary to Peritoneal Dialysis Catheter; An Uncommon Complication - Uraik Fernando Hernández-Bustos; Jonathan Salgado-Vives; Dante Alejandro Saldivar-Vera; Pedro Antonio Alvarado-Bahena; Enrique Chávez-Serna (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Introduction: One of the rare complications of peritoneal dialysis catheter placement is intestinal perforation, often with a late presentation. Clinical case: The case of a 28-year-old female with a history of placement of a Tenckhoff catheter in March 2019 is presented. She came to the emergency service in June 2020 for referring a catheter discharge by anal region. Conclusions: Due to the low incidence of this complication, there is no standard management. In general, removal of the catheter with primary closure of the defect appears to be the best alternative.